Contact Tracing Device for Workplace Using FAVORIOT Platform - Samsul, Siti Hajar; Wan Mahmud, Wan Mahani Hafizah (Evolution in Electrical and Electronic Engineering, 2022)
The pandemic of COVID-19 has brought serious social and health problems to people in this year. To decrease its negative influence, many contact tracing systems and applications have been identified and implemented by governments of the world rapidly. This project developed close contact as the database in the FAVORIOT platform using the BLE tag. The BLE tag combines ESP32 TTGO as a microcontroller and uses Bluetooth Low Energy as the sensor to detect close contact. The BLE tag was developed to obtain data from Bluetooth and then transfer the data by internet connection to the FAVORIOT platform. Before the BLE tag is used, it needs to be registered generic name, user ID, and username for the sensor. In the FAVORIOT platform, the received data will be processed and displayed. A dashboard was designed in the FAVORIOT to easily monitor the time interval of close contact with a person and the number of active contacts. This project's result is to easily monitor users to trace close contact at the workplace. As the BLE tag prototype, it works as intended when it is activated, scans BLE around it, and looks for the generic name, which also sensors themselves. The lower the RSSI values, the stronger the sensor's signal strength will scan another BLE tag. The proposed tool may also be used for contact tracing or large-scale monitoring in future health crises. Also, there will be further discussion on the improvement of contact tracing projects, such as adding a haptic buzzer so that the user can be more alert when close contact is identified. In addition, the guard at the workplace can access and print out the employee's database and display it at the main entrance office. This will ensure that employees will be easy to trace without access to FAVORIOT and can be implemented with various applications in the future product.